Thermoacoustic Properties of Combustion Chambers with Concentrated Parameters - E. V. Toropov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2004)
In order to describe dynamic properties of combustion chambers of heat power engineering plants method of concentrated acoustic parameters is used to investigate regularities of initiation and development of periodic processes including their own properties and force oscillations. The results of the present paper are recommended for application in designing and improvement of the existing pulsating combustion chambers.